Comparison and Analytical Impact of Various Methods of Contraception on Liver Profile of Females of Sindh Province - Hanozia Shah, Jamshed Warsi, Zulfiqar Laghari, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To Compare and Analyze the impact of different methods of contraception on liver Profile of females of Sindh province. Study setting: This is a comparative cross-sectional study that was done at Liaquat university of medical and health sciences Jamshoro, at center 'A' of reproductive health services. Methodology: 300 participants from Hyderabad Sindh were selected. Females aged 20 to 40 years and those on an individual method of contraception were selected.300 females were selected for this study. Among them, 138 ( 46.0%) were residents of rural Sindh whereas162(54.0%) belonged tour ban Sindh. Consent from participants both verbal and written was taken. A structured questionnaire was filled out for demographic characteristics following detailed history. Blood Sampling was done for liver function test. Results: The results showed that present users of contraceptives generally had significantly greater liver parameters biliru bin, gamma GT, SGPT, and Alkaline phosphates compared to non-users ( p-value= <0.05). Bilirubin level was considerably greater among women who were using the contraceptive methods DMPA injection (0.72±0.24), Jadelle (0.54±0.26), IUCD (0.44±0.18) than the corresponding values for nonusers (0.43±0.194) [control 0.43±0.194 vs DMPA injection(0.72±0.24)vsJadelle(0.54±0.26)vsIUCD(0.44±0.18),P-value=<0.05)]. Gama GT level was considerably greater among women who were using the contraceptive methods Jadelle (20.36±11.97), Oral (14.00±3.2) than the corresponding values for non users (15.42±7.36)[control 15.42±7.36 Jadelle (20.36±11.97) vs Oral (14.00±3.2) Oral (14.00±3.2) P-value = <0.05)]. SGPT level was considerably greater among women who were using the contraceptive methods DMPA injection (32.68±18.37), Jadelle (31.34±14.13), IUCD (29.66±14.62), Tubal ligation (18.00±0.00) than the corresponding values for nonusers (25.39±14.59) [control25.39±14.59 vs injection (32.68±18.37) vs Jadelle (31.34±14.13) vs IUCD (29.66±14.62), Tubal ligation (18.00±0.00) P-value = < 0.05)]. Alkaline Phosphatase level was considerably greater among women who were using the contraceptive methods DMPA injection (114.65±48.19),Jadelle (99.28±38.076),IUCD(101.74±42.23)Oral(78.89±21.70)TubalLigation(62.50±2.12)Condom (94.62±25.67) than the corresponding values for nonusers (131.51±59.04) [control131.51±59.04 vs DMPA injection (114.65±48.19) vs Jadelle (99.28±38.076) vs IUCD(101.74±42.23),Oral(78.89±21.70)Tuballigation (62.50±2.12)Condom(94.62±25.67)P-value= < 0.05)]. Conclusion: The impact on the liver of different contraceptive methods was compared and analyzed in the population of Sindh. Keywords: DMPA (depot- medroxy progester one acetate), Implant, Oral Pills, IUCD (intrauterine contraceptive device), tuballigation.